Poverty, inequality and health an international perspective - Leon, David A.; Walt, Gillian (Oxford : Oxford University Press, 2000)
This work raises new and critical issues about health inequalities. It provides an international perspective on this problem, with contributions from a wide range of disciplines and from the developed and developing world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Poor -- Medical care -- Cross-cultural studies; Poor -- Diseases -- Cross-cultural studies; Poor -- Medical care -- Developing countries -- Cross-cultural studies